Reactivation of FMR1 by CRISPR/Cas9-Mediated Deletion of the Expanded CGG-Repeat of the Fragile X Chromosome - Xie, Nina; Gong, He; Suhl, Joshua A.; Chopra, Pankaj; Wang, Tao; Warren, Stephen T. (PLOS ONE, 2016)
Fragile X syndrome (FXS) is a common cause of intellectual disability that is most often due to a CGG-repeat expansion mutation in the FMR1 gene that triggers epigenetic gene silencing. Epigenetic modifying drugs can only transiently and modestly induce FMR1 reactivation in the presence of the elongated CGG repeat. As a proof-of-principle, we excised the expanded CGG-repeat in both somatic cell hybrids containing the human fragile X chromosome and human FXS iPS cells using the CRISPR/Cas9 genome editing. We observed transcriptional reactivation in approximately 67% of the CRISPR cut hybrid colonies and in 20% of isolated human FXS iPSC colonies. The reactivated cells produced FMRP and exhibited a decline in DNA methylation at the FMR1 locus. These data demonstrate the excision of the expanded CGG-repeat from the fragile X chromosome can result in FMR1 reactivation.